ChemInform Abstract: AgCu3V4O12: A Novel Perovskite Containing Mixed‐Valence Silver Ions. Issue 8 (25th February 2014) - Akizuki, Yasuhide; Yamada, Ikuya; Fujita, Koji; Akamatsu, Hirofumi; Irifune, Tetsuo; Tanaka, Katsuhisa
Abstract The new title compound is prepared by solid state reaction of Ag2O, CuO, VO2, and V2O5 in the molar ratio 1:6:6:1 (Pt capsule, 15 GPa, 1373 K, 20 min).